Resepsi Alquran Santri Pondok Pesantren MBI Mambaul Falah Bawean - Sholihan, Sholihan; Puspitasari, Ria (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2024)
This research examined the reception of the Qur'an among the students of MBI Mambaul Falah Bawean Islamic Boarding School. The Quran is understood as an ideology that gives rise to positive behaviour in social tradition. The concept of 'living Quran' is the basis of this research to identify three models of reception: exegesis, aesthetic and functional. Using a qualitative approach, this study highlights the Qur'an as a source of knowledge and a guide to life for students in shaping good morals, character and attitudes to become servants who have good spiritual and social relationships, especially later when Khidmah in the community. The findings of the author's research show that Qur'anic reception is not only an academic endeavour but also a life practice that inspires and motivates santri to live a meaningful life. This research highlights the importance of contextualised and responsive Islamic education in meeting the challenges of the times in the contemporary era.